A putative nuclear copper chaperone promotes plant immunity in Arabidopsis. (31st August 2020) - Chai, Long-Xiang; Dong, Kai; Liu, Song-Yu; Zhang, Zhen; Zhang, Xiao-Peng; Tong, Xin; Zhu, Fei-Fan; Zou, Jing-Ze; Wang, Xian-Bing
Abstract : A new putative copper chaperone localizes in the nucleus and improves plant defense response in Arabidopsis thaliana . Abstract: Copper is essential for many metabolic processes but must be sequestrated by copper chaperones. It is well known that plant copper chaperones regulate various physiological processes. However, the functions of copper chaperones in the plant nucleus remain largely unknown. Here, we identified a putative copper chaperone induced by pathogens (CCP) in Arabidopsis thaliana . CCP harbors a classical MXCXXC copper-binding site (CBS) at its N-terminus and a nuclear localization signal (NLS) at its C-terminus. CCP mainly formed nuclear speckles in the plant nucleus, which requires the NLS and CBS domains. Overexpression of CCP induced PR1 expression and enhanced resistance against Pseudomonas syringae pv. tomato DC3000 compared with Col-0 plants. Conversely, two CRISPR/Cas9-mediated ccp mutants were impaired in plant immunity. Further biochemical analyses revealed that CCP interacted with the transcription factor TGA2 in vivo and in vitro . Moreover, CCP recruits TGA2 to the PR1 promoter sequences in vivo, which induces defense gene expression and plant immunity. Collectively, our results have identified a putative nuclear copper chaperone required for plant immunity and provided evidence for a potential function of copper in the salicylic pathway.